Antimicrobial activity in leaves of Capsicum frutescens L. cvs. (Labuyo and Haba) - Ubaldo, Charisse D.; Lizada, Ma. Concepcion C. (2005)
ABSTRACT Leaf extracts of Capsicum frutescens Linn. cvs. 'Labuyo' and 'Haba' were evaluated for antimicrobial activity against Escherichia coli and Staphylococcus aureus using the disk diffusion assay. Both the aqueous and methanol extracts of both C. frutescens cultivars inhibited the growth of both test organisms, although the inhibition by aqueous extracts was more consistent and pronounced against E. coli. In contrast, hexane extracts showed no significant activity against either organism. The pattern of inhibition indicates that components active against E. coli include polar compounds that can be taken up into water. To further characterize the constituents with antimicrobial activity, the fractionation of the methanol extracts by paper chromatography in butanol-acetic acid-water (90:22.5:37.5 v/v) was undertaken. The chromatograms generated by measuring the activity of 1-cm fractions showed that fractions exhibiting greater antimicrobial activity of 1-cm fractions showed that fractions exhibiting greater antimicrobial activity against E. coli are less polar than those active against S. aureus. Contrary to observations with the crude extracts, the aggregate activity of the fractionated extracts proved to be higher in S. aureus. Further characterization of the active fractions was attempted by spraying chromatograms with color reagents. However, a positive reaction was obtained only with I2 and permanganate, which are non-specific reagents.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Peppers